Learning NOT to Forget: A Reflective Narrative on Language and Identity in the Era of Multiculturalism - Sevilla Morales, Henry (Universidad de Costa Rica, Sede de Occidente, 2014)
The aim of this paper is to verbalize and analyze the experiences of a Costa Rican EFL learner in light of current theory on language and identity. This is a reflective narrative that arises as a response to an article by Benjamin Baez entitled “Learning to Forget: Reflections on Identity and Language”. In this article, Baez narrates and analyzes his experience as a Puerto Rican Spanish speaker learning English in the United States at a time (1978) when the melting pot policy was at its best. Conversely, the present article explores the status quo of language and identity at an epoch when such philosophy is being overtaken by that of the salad bowl, which stresses the need for cultural pluralism across societies. This reflective narrative helps us understand the ideological transformation the world needs to undergo before it can finally claim multiculturalism.